Association of Birth Order With Mental Health Problems, Self-Esteem, Resilience, and Happiness Among Children: Results From A-CHILD Study - Fukuya, Yoshifumi; Fujiwara, Takeo; Isumi, Aya; Doi, Satomi; Ochi, Manami (Frontiers in Psychiatry, 2021)
Objective: This study aimed to investigate the association of birth order with mental health problems, self-esteem, resilience, and happiness among children aged 9 to 10 years. Methods: This was a cross-sectional study using data from the Adachi Child Health Impact of Living Difficulty (A-CHILD) study, which was a population-based study of children in fourth grade in public schools in Adachi City, Tokyo, Japan in 2018 (N=3744). Parent-rated Strengths and Difficulties Questionnaire (SDQ) and self-rated resilience, happiness, and self-esteem score were used to assess child mental health. Multiple regression analysis for continuous outcomes and logistic regression for dichotomous outcomes were used to examine the association of birth order with mental health problems, resilience, happiness, and self-esteem. The analysis was controlled for child sex, mother’s age, mother’s education, caregiver’s depressive symptoms, household income, and living with grandparents. Results: Last-borns showed the lowest total difficulties score in the SDQ, while only children showed the highest (p<0.001). The highest prosocial behaviors score was found among last-borns (p<0.001). Resilience score was also highest among last-borns, followed by first-borns, middle-borns, and only children. The lowest happiness score was found among middle-borns. Self-esteem score did not differ by sibling types. These associations were similar in the adjusted model and dichotomized outcomes model. Conclusions: Differential impacts of birth order on child mental health, for both positive and negative sides, were found. Further research is warranted to elucidate the mechanism of the association between birth order and the development of behavior problems and the positive aspects such as resilience, happiness, and self-esteem among children.